Digestive tract stent biodegradable material and preparation method thereof

By using a variety of bio-based materials and inorganic fillers, combined with twin-screw extrusion, a digestive tract stent biodegradable material with excellent mechanical properties and biocompatibility was prepared, and the mechanical properties of biodegradable stents in the prior art were solved. The deficiencies in degradation rate control have achieved more efficient material performance and degradation performance.

CN119158090AInactive Publication Date: 2024-12-20SUZHOU STERN MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411069562.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing biodegradable stents have shortcomings in mechanical properties, degradation rate control and local tissue reactions, which are difficult to meet the needs of digestive tract stents.

Method used

Use bio-based materials such as polylactic acid, polycaprolactone, albumin, collagen, polyhydroxyacetic acid, polyhydroxybutyrate, etc., combined with antibacterial antibacterial agents, lubricants, antioxidants and inorganic fillers, and extrude through twin screws. Methods: The digestive tract stent biodegradable material with excellent mechanical properties and biocompatibility was prepared, and the degradation rate was controlled by adjusting the formula ratio.

Benefits of technology

It improves the biocompatibility, mechanical properties and degradation properties of materials, meets the needs of different application scenarios, reduces environmental pollution, reduces production costs, and expands the application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158090A_ABST
    Figure CN119158090A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medical functional materials, and discloses an alimentary canal stent biodegradable material and a preparation method thereof, and the alimentary canal stent biodegradable material is prepared from the following raw materials by weight: 50-70 parts of polylactic acid; 20 to 40 parts of polycaprolactone; 5-9 parts of albumin; 4 to 9 parts of collagen; 3-6 parts of polyglycolic acid; 2 to 4 parts of polyhydroxybutyrate; 6 to 10 parts of hydroxybutyl acrylate; 4-6 parts of an auxiliary agent; 2-4 parts of an activator; 2-7 parts of an inorganic filler; and 30 to 50 parts of butylene terephthalate. The preparation method is reasonable in design, various bio-based and biodegradable components such as polylactic acid, polycaprolactone and polyglycolic acid are utilized, the components can be decomposed by microorganisms in the natural environment, pollution to the environment is reduced, the biocompatibility of the material is improved by adding albumin and collagen, and the service life of the material is prolonged. And the method is more suitable for application in the fields of medical treatment and health.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical functional materials, and in particular to a digestive tract stent biodegradable material and a preparation method thereof. Background Art

[0002] Degradable digestive tract stents are medical devices used in digestive tract reconstruction surgery in anorectal and gastrointestinal surgery to assist in anastomosis or anastomosis after short-term diversion of the digestive tract. Degradable digestive tract stents can support or block the cavity, which is helpful for the reconstruction and anastomosis of the digestive tract (such as the intestine). The intestinal stent in the prior art has a tubular structure with a thin middle and thick ends. This structure can make the intestinal stent less likely to move during use, such as a degradable intestinal stapler disclosed in publication number CN115054304A, which is an integrally formed middle section and a second main body, and the middle section and the second main body are passages, and the second main body also uses degradable materials. After the digestive tract reconstruction and healing period, the degradable digestive tract stent needs to be detached regularly to restore the digestive tract to smoothness and function. Therefore, when preparing a degradable digestive tract stent, degradable materials are usually used. The degradable digestive tract stent made of degradable materials can be disintegrated and discharged under the action of intestinal peristalsis after being set to a controllable in vivo fragmentation cycle.

[0003] Digestive tract diseases, such as esophageal cancer and gastric cancer, often lead to stenosis or occlusion of the digestive tract, seriously affecting the quality of life of patients. Traditional treatment options include surgery and metal stent implantation. However, these methods have problems such as large trauma and many complications. In recent years, biodegradable stents have attracted attention due to their good biocompatibility and degradability. However, existing biodegradable stents still have deficiencies in mechanical properties, degradation rate control, and local tissue reactions; therefore, we propose a biodegradable material for digestive tract stents and a preparation method thereof to solve this problem. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of existing biodegradable stents in terms of mechanical properties, degradation rate control and local tissue reaction, and to propose a digestive tract stent biodegradable material and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A digestive tract stent biodegradable material, made from the following raw materials in parts by weight:

[0007] Polylactic acid 50-70 parts;

[0008] Polycaprolactone 20-40 parts;

[0009] Albumin 5-9 parts;

[0010] 4-9 parts of collagen;

[0011] 3-6 parts of polyglycolic acid;

[0012] 2-4 parts of polyhydroxybutyrate; 6-10 parts of hydroxybutyl acrylate;

[0013] 4-6 parts of additives;

[0014] 2-4 parts of activator;

[0015] 2-7 parts of inorganic filler;

[0016] 30-50 parts of butylene terephthalate.

[0017] Preferably, the auxiliary agent is composed of the following substances in percentage by weight:

[0018] Antibacterial and antimicrobial agents: nano silver ion fluorite, sodium alginate, triethyl or tri-n-butyl quaternary ammonium salt, 5-15%;

[0019] Lubricant: calcium stearate, zinc stearate, polyoxyethylene ester, stearic acid amide or dimethyl silicone oil, 30-50%;

[0020] Antioxidant: antioxidant 1010, antioxidant 330, antioxidant TZP or antioxidant BHT, 25-45%;

[0021] Nucleating agent: calcium carbonate, silicon dioxide, talc or montmorillonite, 5-10%.

[0022] Preferably, the active agent is composed of the following substances in percentage by weight:

[0023] Silane coupling agent 40-45%;

[0024] Titanate coupling agent 20-25%;

[0025] Borate coupling agent 20-25%;

[0026] Sucrose fatty acid esters 10-15%.

[0027] The present invention also provides a method for preparing the above-mentioned digestive tract stent biodegradable material, comprising the following steps:

[0028] S1, raw material pretreatment: take 50-70 parts of polylactic acid, 20-40 parts of polycaprolactone, 3-6 parts of polyglycolic acid, 2-4 parts of polyhydroxybutyrate, 6-10 parts of hydroxybutyl acrylate, and 30-50 parts of butylene terephthalate; put them into an ultrafine grinder for grinding and mixing to obtain a solid powder for standby use;

[0029] S2. Preparation of additives: 5-15% of antibacterial and antimicrobial agent, 30-50% of lubricant, 25-45% of antioxidant, and 5-10% of nucleating agent are put into a high-speed mixer and mixed evenly to obtain an additive for standby use;

[0030] S3, preparation of activator: 40-45% of silane coupling agent, 20-25% of titanate coupling agent, 20-25% of borate coupling agent, and 10-15% of sucrose fatty acid ester are put into a grinder and crushed, the powder obtained by crushing is put into a mixer, and a solvent is added and mixed to obtain an activator for standby use;

[0031] S4, mixing: taking the solid powder obtained in S1, 4-6 parts of the auxiliary agent obtained in S2, 2-4 parts of the activator obtained in S3 and 2-7 parts of the inorganic filler, putting them into a mixer, mixing, and obtaining a mixed material;

[0032] S5, extrusion: adding the mixture prepared in S4 into a twin-screw extruder for heating, melting and extrusion;

[0033] S6, cooling and solidification: cooling and solidifying the extruded material through a cooling water tank;

[0034] S7, cutting and molding: cutting the cooled material into the required size, and finally molding it by stamping or injection molding to obtain a molded product;

[0035] S8, post-processing: surface treatment of molded products, such as grinding, cleaning or coating, to improve their performance and appearance;

[0036] S9. Quality inspection: Conduct mechanical property, biodegradability and biocompatibility tests on molded products to ensure compliance with application standards.

[0037] Preferably, the mixing time in S3 is 30-50 min, the mixing temperature of the mixer is controlled at 80-90° C., and the mixture is cooled to room temperature after mixing.

[0038] Preferably, the step S4 includes the following steps:

[0039] S41, pre-mixing: at room temperature, control the mixer speed to 50-100 RPM and mix the materials at a low speed;

[0040] S42, heating and melting: controlling the mixer temperature at 120-169°C and the speed at 300-500RPM to heat, melt and mix the materials at medium speed;

[0041] S43, high-speed mixing: control the mixer temperature at 160-200℃ and the speed at 500-800RPM to achieve high-speed mixing;

[0042] S44, cooling and discharging: reduce the temperature of the mixer to 100-120°C and the speed to 50-100RPM to achieve discharging.

[0043] Preferably, in S5, the barrel temperature of the twin-screw extruder is set to 160-190° C., and the screw speed is set to 200-450 RPM.

[0044] Preferably, in said S9, when testing the biodegradability of the molded product, the following steps are included:

[0045] S91. Preparation of enzyme solution: According to the type of polymer to be tested, select a suitable enzyme and prepare a solution of a certain concentration.

[0046] S92. Sample preparation: Cut the samples to be tested into standard sizes and sterilize them.

[0047] S93. Degradation experiment: Immerse the sample in enzyme solution and keep it at the temperature for optimal enzyme activity.

[0048] S94. Regular testing: Take out samples regularly to test their weight loss rate and molecular weight change, so as to determine the biodegradability of the molded products.

[0049] Compared with the prior art, the present invention provides a digestive tract stent biodegradable material and a preparation method thereof, which has the following beneficial effects:

[0050] (1) The material uses a variety of bio-based and biodegradable components, such as polylactic acid, polycaprolactone and polyglycolic acid, which can be decomposed by microorganisms in the natural environment, reducing pollution to the environment;

[0051] (2) By adding albumin and collagen, the biocompatibility of the material is improved, making it more suitable for applications in the medical and health fields, such as tissue engineering scaffolds and drug delivery systems;

[0052] (3) The addition of polyhydroxybutyrate and polyhexyl acrylate improves the mechanical properties and processing properties of the material, making it have better strength and toughness, making it suitable for use in packaging, agriculture, medical devices and other fields;

[0053] (4) By adjusting the proportion of components in the formula, the degradation rate of the material can be controlled within a certain range to meet the needs of different application scenarios;

[0054] (5) The bio-based resin and additives are mixed to improve the processing fluidity of the material, making it easier to produce on traditional plastic processing equipment, reducing production costs and improving production efficiency;

[0055] (6) The addition of inorganic fillers and activators can enhance the material's heat resistance, flame retardancy, conductivity and other functional properties, expanding the material's application areas

[0056] (7) The twin-screw melt extrusion method ensures the full fusion and plasticization of the polymer materials. This method can improve the uniformity of material mixing, thereby obtaining products with uniform performance;

[0057] (8) By monitoring the material temperature during the mixing process, the degradation of material components due to excessive temperature can be avoided. Different stirring speeds can be used according to different temperature stages to ensure mixing uniformity and improve material preparation efficiency and quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 The present invention provides a flow chart of the method for preparing the biodegradable material for the digestive tract stent. DETAILED DESCRIPTION

[0059] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0060] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0061] Embodiment 1

[0062] A digestive tract stent biodegradable material, made from the following raw materials in parts by weight:

[0063] 50 parts of polylactic acid;

[0064] 20 parts of polycaprolactone;

[0065] Albumin 5 parts;

[0066] 4 parts of collagen;

[0067] 3 parts of polyglycolic acid;

[0068] 2 parts of polyhydroxybutyrate; 6 parts of hydroxybutyl acrylate;

[0069] 4 parts of additives;

[0070] 2 parts of activator;

[0071] 2 parts of inorganic filler;

[0072] 30 parts of butylene terephthalate.

[0073] In this embodiment, the additive is composed of the following substances in percentage by weight:

[0074] Antibacterial and antimicrobial agents: nano silver ion fluorite, sodium alginate, triethyl or tri-n-butyl quaternary ammonium salt, 15%;

[0075] Lubricant: calcium stearate, zinc stearate, polyoxyethylene ester, stearic acid amide or dimethyl silicone oil, 35%;

[0076] Antioxidant: antioxidant 1010, antioxidant 330, antioxidant TZP or antioxidant BHT, 45%;

[0077] Nucleating agent: calcium carbonate, silica, talc or montmorillonite, 5%.

[0078] In this embodiment, the active agent is composed of the following substances in percentage by weight:

[0079] Silane coupling agent 45%;

[0080] Titanate coupling agent 20%;

[0081] Borate coupling agent 20%;

[0082] Sucrose fatty acid esters 15%.

[0083] Reference Figure 1 The present invention also provides a method for preparing the above-mentioned digestive tract stent biodegradable material, comprising the following steps:

[0084] S1, raw material pretreatment: take 50 parts of polylactic acid, 20 parts of polycaprolactone, 3 parts of polyglycolic acid, 2 parts of polyhydroxybutyrate, 6 parts of hydroxybutyl acrylate, and 30 parts of butylene terephthalate; put them into an ultrafine grinder for grinding and mixing to obtain a solid powder for standby use;

[0085] S2, preparation of auxiliary agent: take 15% of antibacterial and antimicrobial agent, 35% of lubricant, 45% of antioxidant, and 5% of nucleating agent, put them into a high-speed mixer, mix them evenly, and prepare auxiliary agent for standby use;

[0086] S3, preparation of activator: 45% of silane coupling agent, 20% of titanate coupling agent, 20% of borate coupling agent, and 15% of sucrose fatty acid ester are put into a grinder and crushed, the powder obtained by crushing is put into a mixer, and a solvent is added and mixed to obtain an activator, which is set aside;

[0087] S4, mixing: taking the solid powder prepared in S1, 4 parts of the auxiliary agent prepared in S2, 2 parts of the activator prepared in S3 and 2 parts of the inorganic filler, putting them into a mixer, mixing, and preparing a mixed material;

[0088] S5, extrusion: adding the mixture prepared in S4 into a twin-screw extruder for heating, melting and extrusion;

[0089] S6, cooling and solidification: cooling and solidifying the extruded material through a cooling water tank;

[0090] S7, cutting and molding: cutting the cooled material into the required size, and finally molding it by stamping or injection molding to obtain a molded product;

[0091] S8, post-processing: surface treatment of molded products, such as grinding, cleaning or coating, to improve their performance and appearance;

[0092] S9. Quality inspection: Conduct mechanical property, biodegradability and biocompatibility tests on molded products to ensure compliance with application standards.

[0093] In this embodiment, the mixing time in S3 is 50 minutes, the mixing temperature of the mixer is controlled at 80-90° C., and the mixture is cooled to room temperature after mixing.

[0094] In this embodiment, S4 includes the following steps:

[0095] S41, pre-mixing: at room temperature, control the mixer speed to 50-100 RPM and mix the materials at a low speed;

[0096] S42, heating and melting: controlling the mixer temperature at 120-169°C and the speed at 300-500RPM to heat, melt and mix the materials at medium speed;

[0097] S43, high-speed mixing: control the mixer temperature at 160-200℃ and the speed at 500-800RPM to achieve high-speed mixing;

[0098] S44, cooling and discharging: reduce the temperature of the mixer to 100-120°C and the speed to 50-100RPM to achieve discharging.

[0099] In this embodiment, in S5, the barrel temperature of the twin-screw extruder is set to 160-190° C., and the screw speed is set to 200-450 RPM.

[0100] In this embodiment, in S9, when detecting the biodegradability of the molded product, the following steps are included:

[0101] S91. Preparation of enzyme solution: According to the type of polymer to be tested, select a suitable enzyme and prepare a solution of a certain concentration.

[0102] S92. Sample preparation: Cut the samples to be tested into standard sizes and sterilize them.

[0103] S93. Degradation experiment: Immerse the sample in enzyme solution and keep it at the temperature for optimal enzyme activity.

[0104] S94. Regular testing: Take out samples regularly to test their weight loss rate and molecular weight change, so as to determine the biodegradability of the molded products.

[0105] Embodiment 2

[0106] A digestive tract stent biodegradable material, made from the following raw materials in parts by weight:

[0107] 70 parts of polylactic acid;

[0108] 40 parts of polycaprolactone;

[0109] Albumin 5 parts;

[0110] 4 parts of collagen;

[0111] 3 parts of polyglycolic acid;

[0112] 2 parts of polyhydroxybutyrate; 6 parts of hydroxybutyl acrylate;

[0113] 4 parts of additives;

[0114] 2 parts of activator;

[0115] 2 parts of inorganic filler;

[0116] 30 parts of butylene terephthalate.

[0117] In this embodiment, the additive is composed of the following substances in percentage by weight:

[0118] Antibacterial and antimicrobial agents: nano silver ion fluorite, sodium alginate, triethyl or tri-n-butyl quaternary ammonium salt, 15%;

[0119] Lubricant: calcium stearate, zinc stearate, polyoxyethylene ester, stearic acid amide or dimethyl silicone oil, 35%;

[0120] Antioxidant: antioxidant 1010, antioxidant 330, antioxidant TZP or antioxidant BHT, 45%;

[0121] Nucleating agent: calcium carbonate, silica, talc or montmorillonite, 5%.

[0122] In this embodiment, the active agent is composed of the following substances in percentage by weight:

[0123] Silane coupling agent 45%;

[0124] Titanate coupling agent 20%;

[0125] Borate coupling agent 20%;

[0126] Sucrose fatty acid esters 15%.

[0127] Reference Figure 1 The present invention also provides a method for preparing the above-mentioned digestive tract stent biodegradable material, comprising the following steps:

[0128] S1, raw material pretreatment: take 70 parts of polylactic acid, 40 parts of polycaprolactone, 3 parts of polyglycolic acid, 2 parts of polyhydroxybutyrate, 6 parts of hydroxybutyl acrylate, and 30 parts of butylene terephthalate; put them into an ultrafine grinder for grinding and mixing to obtain a solid powder for standby use;

[0129] S2, preparation of auxiliary agent: take 15% of antibacterial and antimicrobial agent, 35% of lubricant, 45% of antioxidant, and 5% of nucleating agent, put them into a high-speed mixer, mix them evenly, and prepare auxiliary agent for standby use;

[0130] S3, preparation of activator: 45% of silane coupling agent, 20% of titanate coupling agent, 20% of borate coupling agent, and 15% of sucrose fatty acid ester are put into a grinder and crushed, the powder obtained by crushing is put into a mixer, and a solvent is added and mixed to obtain an activator, which is set aside;

[0131] S4, mixing: taking the solid powder prepared in S1, 4 parts of the auxiliary agent prepared in S2, 2 parts of the activator prepared in S3 and 2 parts of the inorganic filler, putting them into a mixer, mixing, and preparing a mixed material;

[0132] S5, extrusion: adding the mixture prepared in S4 into a twin-screw extruder for heating, melting and extrusion;

[0133] S6, cooling and solidification: cooling and solidifying the extruded material through a cooling water tank;

[0134] S7, cutting and molding: cutting the cooled material into the required size, and finally molding it by stamping or injection molding to obtain a molded product;

[0135] S8, post-processing: surface treatment of molded products, such as grinding, cleaning or coating, to improve their performance and appearance;

[0136] S9. Quality inspection: Conduct mechanical property, biodegradability and biocompatibility tests on molded products to ensure compliance with application standards.

[0137] In this embodiment, the mixing time in S3 is 50 minutes, the mixing temperature of the mixer is controlled at 80-90° C., and the mixture is cooled to room temperature after mixing.

[0138] In this embodiment, S4 includes the following steps:

[0139] S41, pre-mixing: at room temperature, control the mixer speed to 50-100 RPM and mix the materials at a low speed;

[0140] S42, heating and melting: controlling the mixer temperature at 120-169°C and the speed at 300-500RPM to heat, melt and mix the materials at medium speed;

[0141] S43, high-speed mixing: control the mixer temperature at 160-200℃ and the speed at 500-800RPM to achieve high-speed mixing;

[0142] S44, cooling and discharging: reduce the temperature of the mixer to 100-120°C and the speed to 50-100RPM to achieve discharging.

[0143] In this embodiment, in S5, the barrel temperature of the twin-screw extruder is set to 160-190° C., and the screw speed is set to 200-450 RPM.

[0144] In this embodiment, in S9, when detecting the biodegradability of the molded product, the following steps are included:

[0145] S91. Preparation of enzyme solution: According to the type of polymer to be tested, select a suitable enzyme and prepare a solution of a certain concentration.

[0146] S92. Sample preparation: Cut the samples to be tested into standard sizes and sterilize them.

[0147] S93. Degradation experiment: Immerse the sample in enzyme solution and keep it at the temperature for optimal enzyme activity.

[0148] S94. Regular testing: Take out samples regularly to test their weight loss rate and molecular weight change, so as to determine the biodegradability of the molded products.

[0149] Embodiment 3

[0150] A digestive tract stent biodegradable material, made from the following raw materials in parts by weight:

[0151] 70 parts of polylactic acid;

[0152] 20 parts of polycaprolactone;

[0153] Albumin 5 parts;

[0154] 4 parts of collagen;

[0155] 3 parts of polyglycolic acid;

[0156] 2 parts of polyhydroxybutyrate; 6 parts of hydroxybutyl acrylate;

[0157] 4 parts of additives;

[0158] 2 parts of activator;

[0159] 2 parts of inorganic filler;

[0160] 30 parts of butylene terephthalate.

[0161] In this embodiment, the additive is composed of the following substances in percentage by weight:

[0162] Antibacterial and antimicrobial agents: nano silver ion fluorite, sodium alginate, triethyl or tri-n-butyl quaternary ammonium salt, 15%;

[0163] Lubricant: calcium stearate, zinc stearate, polyoxyethylene ester, stearic acid amide or dimethyl silicone oil, 35%;

[0164] Antioxidant: antioxidant 1010, antioxidant 330, antioxidant TZP or antioxidant BHT, 45%;

[0165] Nucleating agent: calcium carbonate, silica, talc or montmorillonite, 5%.

[0166] In this embodiment, the active agent is composed of the following substances in percentage by weight:

[0167] Silane coupling agent 45%;

[0168] Titanate coupling agent 20%;

[0169] Borate coupling agent 20%;

[0170] Sucrose fatty acid esters 15%.

[0171] Reference Figure 1 The present invention also provides a method for preparing the above-mentioned digestive tract stent biodegradable material, comprising the following steps:

[0172] S1, raw material pretreatment: take 70 parts of polylactic acid, 20 parts of polycaprolactone, 3 parts of polyglycolic acid, 2 parts of polyhydroxybutyrate, 6 parts of hydroxybutyl acrylate, and 30 parts of butylene terephthalate; put them into an ultrafine grinder for grinding and mixing to obtain a solid powder for standby use;

[0173] S2, preparation of auxiliary agent: take 15% of antibacterial and antimicrobial agent, 35% of lubricant, 45% of antioxidant, and 5% of nucleating agent, put them into a high-speed mixer, mix them evenly, and prepare auxiliary agent for standby use;

[0174] S3, preparation of activator: 45% of silane coupling agent, 20% of titanate coupling agent, 20% of borate coupling agent, and 15% of sucrose fatty acid ester are put into a grinder and crushed, the powder obtained by crushing is put into a mixer, and a solvent is added and mixed to obtain an activator, which is set aside;

[0175] S4, mixing: taking the solid powder prepared in S1, 4 parts of the auxiliary agent prepared in S2, 2 parts of the activator prepared in S3 and 2 parts of the inorganic filler, putting them into a mixer, mixing, and preparing a mixed material;

[0176] S5, extrusion: adding the mixture prepared in S4 into a twin-screw extruder for heating, melting and extrusion;

[0177] S6, cooling and solidification: cooling and solidifying the extruded material through a cooling water tank;

[0178] S7, cutting and molding: cutting the cooled material into the required size, and finally molding it by stamping or injection molding to obtain a molded product;

[0179] S8, post-processing: surface treatment of molded products, such as grinding, cleaning or coating, to improve their performance and appearance;

[0180] S9. Quality inspection: Conduct mechanical property, biodegradability and biocompatibility tests on molded products to ensure compliance with application standards.

[0181] In this embodiment, the mixing time in S3 is 50 minutes, the mixing temperature of the mixer is controlled at 80-90° C., and the mixture is cooled to room temperature after mixing.

[0182] In this embodiment, S4 includes the following steps:

[0183] S41, pre-mixing: at room temperature, control the mixer speed to 50-100 RPM and mix the materials at a low speed;

[0184] S42, heating and melting: controlling the mixer temperature at 120-169°C and the speed at 300-500RPM to heat, melt and mix the materials at medium speed;

[0185] S43, high-speed mixing: control the mixer temperature at 160-200℃ and the speed at 500-800RPM to achieve high-speed mixing;

[0186] S44, cooling and discharging: reduce the temperature of the mixer to 100-120°C and the speed to 50-100RPM to achieve discharging.

[0187] In this embodiment, in S5, the barrel temperature of the twin-screw extruder is set to 160-190° C., and the screw speed is set to 200-450 RPM.

[0188] In this embodiment, in S9, when detecting the biodegradability of the molded product, the following steps are included:

[0189] S91. Preparation of enzyme solution: According to the type of polymer to be tested, select a suitable enzyme and prepare a solution of a certain concentration.

[0190] S92. Sample preparation: Cut the samples to be tested into standard sizes and sterilize them.

[0191] S93. Degradation experiment: Immerse the sample in enzyme solution and keep it at the temperature for optimal enzyme activity.

[0192] S94. Regular testing: Take out samples regularly to test their weight loss rate and molecular weight change, so as to determine the biodegradability of the molded products.

[0193] The standard parts used in the present invention can all be purchased from the market, and special-shaped parts can be customized according to the instructions and the drawings. The specific connection methods of each part adopt conventional means such as mature bolts, rivets, welding, etc. in the prior art. Machinery, parts and equipment all adopt conventional models in the prior art, and the circuit connection adopts the conventional connection method in the prior art, which will not be described in detail here.

Claims

1. A biodegradable material for a digestive tract stent, Features , made from the following raw materials in parts by weight: Polylactic acid 50-70 parts; Polycaprolactone 20-40 parts; Albumin 5-9 parts; 4-9 parts of collagen; 3-6 parts of polyglycolic acid; 2-4 parts of polyhydroxybutyrate; 6-10 parts of hydroxybutyl acrylate; 4-6 parts of additives; 2-4 parts of activator; 2-7 parts of inorganic filler; 30-50 parts of butylene terephthalate.

2. The digestive tract stent biodegradable material according to claim 1, It is characterized in that The auxiliary agent is composed of the following substances in percentage by weight: Antibacterial and antimicrobial agents: nano silver ion fluorite, sodium alginate, triethyl or tri-n-butyl quaternary ammonium salt, 5-15%; Lubricant: calcium stearate, zinc stearate, polyoxyethylene ester, stearic acid amide or dimethyl silicone oil, 30-50%; Antioxidant: antioxidant 1010, antioxidant 330, antioxidant TZP or antioxidant BHT, 25-45%; Nucleating agent: calcium carbonate, silicon dioxide, talc or montmorillonite, 5-10%.

3. The digestive tract stent biodegradable material according to claim 1, It is characterized in that The active agent is composed of the following substances in percentage by weight: Silane coupling agent 40-45%; Titanate coupling agent 20-25%; Borate coupling agent 20-25%; Sucrose fatty acid esters 10-15%.

4. A method for preparing a biodegradable digestive tract stent material according to any one of claims 1 to 7, It is characterized in that The following steps are involved: S1, raw material pretreatment: take 50-70 parts of polylactic acid, 20-40 parts of polycaprolactone, 3-6 parts of polyglycolic acid, 2-4 parts of polyhydroxybutyrate, 6-10 parts of hydroxybutyl acrylate, and 30-50 parts of butylene terephthalate; put them into an ultrafine grinder for grinding and mixing to obtain a solid powder for standby use; S2. Preparation of auxiliary agent: 5-15% of antibacterial and antimicrobial agent, 30-50% of lubricant, 25-45% of antioxidant and 5-10% of nucleating agent are put into a high-speed mixer and mixed evenly to obtain auxiliary agent for standby use; S3, preparation of activator: 40-45% of silane coupling agent, 20-25% of titanate coupling agent, 20-25% of borate coupling agent, and 10-15% of sucrose fatty acid ester are put into a grinder and crushed, the powder obtained by crushing is put into a mixer, and a solvent is added and mixed to obtain an activator for standby use; S4, mixing: taking the solid powder obtained in S1, 4-6 parts of the auxiliary agent obtained in S2, 2-4 parts of the activator obtained in S3 and 2-7 parts of the inorganic filler, putting them into a mixer, mixing, and obtaining a mixed material; S5, extrusion: adding the mixture prepared in S4 into a twin-screw extruder for heating, melting and extrusion; S6, cooling and solidification: cooling and solidifying the extruded material through a cooling water tank; S7, cutting and molding: cutting the cooled material into the required size, and finally molding it by stamping or injection molding to obtain a molded product; S8, post-processing: surface treatment of molded products, such as grinding, cleaning or coating, to improve their performance and appearance; S9. Quality inspection: Conduct mechanical property, biodegradability and biocompatibility tests on molded products to ensure compliance with application standards.

5. The method for preparing the digestive tract stent biodegradable material according to claim 1, It is characterized in that The mixing time in S3 is 30-50 minutes, the mixing temperature of the mixer is controlled at 80-90° C., and the mixture is cooled to room temperature after mixing.

6. The method for preparing the digestive tract stent biodegradable material according to claim 1, It is characterized in that The S4 includes the following steps: S41, pre-mixing: at room temperature, control the mixer speed to 50-100 RPM and mix the materials at a low speed; S42, heating and melting: control the mixer temperature to 120-169°C and the speed to 300-500RPM to heat, melt and mix the materials at medium speed; S43, high-speed mixing: control the mixer temperature at 160-200℃ and the speed at 500-800RPM to achieve high-speed mixing; S44, cooling and discharging: reduce the temperature of the mixer to 100-120°C and the speed to 50-100RPM to achieve discharging.

7. The method for preparing the digestive tract stent biodegradable material according to claim 1, It is characterized in that In S5, the barrel temperature of the twin-screw extruder is set to 160-190° C., and the screw speed is set to 200-450 RPM.

8. The method for preparing the digestive tract stent biodegradable material according to claim 1, It is characterized in that In said S9, when testing the biodegradability of the molded product, the following steps are included: S91. Preparation of enzyme solution: According to the type of polymer to be tested, select a suitable enzyme and prepare a solution of a certain concentration. S92. Sample preparation: Cut the samples to be tested into standard sizes and sterilize them. S93. Degradation experiment: Immerse the sample in enzyme solution and keep it at the temperature for optimal enzyme activity. S94. Regular testing: Take out samples regularly to test their weight loss rate and molecular weight change, so as to determine the biodegradability of the molded products.